AROUND THE WORLD IN EIGHTY DAYS - Verne, Jules, 1828-1905.; Evans, Tony; Lillie, Stephen (Berkshire, U.K. : Baker Street Press, 2018)
No one would have believed that planet Earth was being watched by creatures more intelligent than humankind...But our planet was not only being watched - soon it would be invaded by monstrous creatures from Mars..
Keywords: Children's stories, English; English fiction